A comparative study of the anti-inflammatory effect of aqueous extract of neem leaf and dexamethasone - Abu Syed Md. Mosaddek; Md. Mamun Ur Rashid (Bangladesh Pharmacological Society, 2008)
The anti-inflammatory effect of aqueous extract of neem leaf (400 mg/kg body weight) was compared with that of dexamethasone (0.75 mg, intraperitoneally) by administering one hour before the formalin injection and once daily for 7 days in rats. The percentage of inhibition of paw edema in case of neem after 3 hours, 6 hours, on day 3, on day 7 after formalin injection were 28%, 40%, 45%, 58% respectively and that in case of dexamethasone after 3 hours, 6 hours, on day 3, on day 7 after formalin injection were 43%, 58%, 61%, 65% respectively. The reduction was statistically significant in each case (p<0.001). The present study suggests that anti-inflammatory effect of neem extract is less than that produced by dexamethasone.